Mad or bad? : the role of staff attributions in dual diagnosis : a thesis presented in partial fulfilment of the requirements for the degree in Master of Science in Psychology at Massey University, Palmerston North, New Zealand - Gregory, Jacqueline (Massey University, 2005)
Research shows a high prevalence of comorbid mental health and substance use disorders, a condition known as dual diagnosis. Dual diagnoses can create significant challenges for the individuals who suffer them, the community and society in which they live, and for helping professions. National and international research shows there are significant barriers to effective treatment for dually diagnosed clients, and New Zealand research has found barriers in three categories - systemic, clinical and attitudinal (Todd, Sellman & Robertson. 2002). The current study is focused on attitudinal barriers, and used a questionnaire developed from Weiner's (1995) theory of social conduct to compare mental health clinician's attributions towards vignettes depicting clients with a mental illness alone, dual diagnosis or a substance use disorder alone. The resulting attributions were analysed to see if responses to the vignettes differed, and to see if attributions responses influenced judgement regarding resource allocation to clients. Results indicated that more negative attributions were made towards the individuals depicted in the dual diagnosis and substance use disorder vignettes, and support was found for the attribution affective stage of Weiner's Theory of Social Conduct.
Keywords: New Zealand; Clinical psychologists -- Attitudes; Dual diagnosis; Discrimination against the mentally ill